2008
DOI: 10.1159/000161579
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic and Anti-Inflammatory Effects of a Novel IκB Kinase β Inhibitor, IMD-0354, in a Mouse Model of Allergic Inflammation

Abstract: Background: Nuclear factor (NF)-κB is a transcription factor known to regulate allergy-associated cytokine and chemokine production related to the induction of inflammation. IκB kinase β (IKKβ), which is responsible for activation of the NF-κB pathway, may be an ideal molecular target to inhibit this process. IMD-0354 [N-(3,5-bis-trifluoromethyl-phenyl)-5-chloro-2-hydroxy-benzamide] is an attractive novel IKKβ inhibitor that prevents the production of inflammatory cytokines in various diseases, although it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 50 publications
3
65
0
Order By: Relevance
“…The production of eotaxin has also been reported to be mediated through NF-kB activation in a mouse model of allergic inflammation [28] and thus, in our study the blockade of the EGFR pathway could potentially have resulted from suppression of NF-kB activation followed by the reductions of IL-6, CINC-1 and eotaxin in BAL. Poynter et al reported that NF-kB repression selectively in airway epithelium significantly reduced the lymphocytes and eosinophils as well as eotaxin and IL-5 in BAL but did not alter AHR in a mouse model of asthma [29].…”
Section: Discussionmentioning
confidence: 65%
“…The production of eotaxin has also been reported to be mediated through NF-kB activation in a mouse model of allergic inflammation [28] and thus, in our study the blockade of the EGFR pathway could potentially have resulted from suppression of NF-kB activation followed by the reductions of IL-6, CINC-1 and eotaxin in BAL. Poynter et al reported that NF-kB repression selectively in airway epithelium significantly reduced the lymphocytes and eosinophils as well as eotaxin and IL-5 in BAL but did not alter AHR in a mouse model of asthma [29].…”
Section: Discussionmentioning
confidence: 65%
“…However, there remains a concern that proteasome inhibition may affect other signaling pathways. IMD-0354 is a synthesized low molecular weight compound that specifically inhibits IKKb, inducing the inhibition of NF-kB activation only in inflammatory conditions, and it was proven that this drug does not inhibit other kinases, proteases, or proteasome-related immune responses (34). No IKKb inhibitor is known to be in the process of clinical application at present, except for IMD-1041, a prodrug of IMD-0354; a phase I study with the IMD-0354 capsule confirmed sufficient safety (20).…”
Section: Discussionmentioning
confidence: 99%
“…9,21,22) This study revealed IMD-0354 dose-dependently attenuated neointimal formation after wire-mediated arterial injury in mice. Thus, IMD-0354 has the potential to prevent restenosis in humans with fewer adverse effects compared to conservative therapies.…”
Section: Discussionmentioning
confidence: 56%
“…The concentrations of the drug were determined according to previous reports. 9,11) Quantitative assessment of arterial neointima: Tissue sections were stained with hematoxylin and eosin (HE) and Elastica van Gieson (EvG). Light microscopic morphometric computer analysis was carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation